2006
DOI: 10.1007/s00421-006-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptational phenomena and mechanical responses during running: effect of surface, aging and task experience

Abstract: The goals of the study were to identify adaptational phenomena in running mechanics over a variety of surfaces due to age related changes in the muscle-tendon units (MTUs) capacities, to examine whether running experience is associated with adaptational effects on running mechanics over a variety of surfaces even at old age, and to investigate whether surface condition affects running mechanics. The investigation was executed on 30 old and 19 young including 29 runners and 20 non-active subjects. In a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 61 publications
(101 reference statements)
6
31
1
Order By: Relevance
“…This gear ratio is defined as the moment arm of the GRF acting about a joint to the moment arm of the counteracting muscle tendon unit (MTU), in this case the m. triceps surae (TS) and the m. quadriceps femoris (QF). Dixon et al (2000), Kakihana et al (2004) and Karamanidis et al (2006) provided data which indicate that the moment arm of the GRF acting about the ankle and knee joints is strongly influenced by environmental conditions. However, there are no studies in the literature of which the authors are aware, which examine the influence of footwear on gearing in the ankle and knee joints during running.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This gear ratio is defined as the moment arm of the GRF acting about a joint to the moment arm of the counteracting muscle tendon unit (MTU), in this case the m. triceps surae (TS) and the m. quadriceps femoris (QF). Dixon et al (2000), Kakihana et al (2004) and Karamanidis et al (2006) provided data which indicate that the moment arm of the GRF acting about the ankle and knee joints is strongly influenced by environmental conditions. However, there are no studies in the literature of which the authors are aware, which examine the influence of footwear on gearing in the ankle and knee joints during running.…”
Section: Introductionmentioning
confidence: 97%
“…It was suggested that running shoes, running surfaces and the running technique could be one of the reasons for running injuries (Taunton et al, 2002;Stefanyshyn et al, 2006;Milner et al, 2006;Cheung et al, 2006). Therefore, several authors systematically changed the technique of locomotion (Cavanagh and Williams, 1982;McMahon et al, 1987;Arendse et al, 2004), the external conditions, e.g., stiffness of the surface (McMahon and Greene, 1979;Ferris et al, 1998;Kerdok et al, 2002;Karamanidis et al, 2006), or the construction of running shoes McNair and Marshall, 1994;Bergmann et al, 1995;Stacoff et al, 2001;Kersting and Brüggemann, 2006) to examine how these specific modifications affect the kinetics and kinematics while running. An important topic in gait analysis is load management, distribution and redistribution within the locomotor system (DeVita and Hortobagyi, 2000;Andriacchi et al, 2004;Mündermann et al, 2004Mündermann et al, , 2005Hunt et al, 2006;Jenkyn et al, 2008;Kemp et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Reductions in ankle strength in the elderly have been attributed to changes in muscle architecture such as decreases in muscle volume, shortening of fascicles, and decreases in pennation angle (Kubo et al, 2003a;Karamanidis et al, 2006). Decreases in plantarflexor volume and physiological cross-sectional area attributable to age-related sarcopenia are substantial contributors to loss of muscle strength in the elderly (Morse et al, 2005c).…”
Section: Introductionmentioning
confidence: 98%
“…However, during sprinting, the deficit remained roughly the same showing only slightly greater decline (15% and 27%) compared with the young athletes. A previous study [14] with slower running speed (2.7 m s…”
Section: Running and Sprintingmentioning
confidence: 99%